Gelatine-Based Antioxidant Packaging Containing Caesalpinia decapetala and Tara as a Coating for Ground Beef Patties - María Gabriela Gallego; Michael H. Gordon; Francisco Segovia; María Pilar Almajano Pablos (MDPI AG, 2016)
The development of antioxidant-active packaging has numerous advantages, such as the reduction of synthetic additives in food, the reduction of plastic waste and food protection against oxidation reactions. Different concentrations of extracts of the plants Caesalpinia decapetala (CD) and Caesalpinia spinosa "Tara" (CS) were incorporated into gelatine films as natural antioxidants. The physical, mechanical and antioxidant properties of these films were studied. Films containing plant extracts at a high concentration had lower tensile strength with higher elongation at break points, compared to the control film (p < 0.05). Films exhibited antioxidant activity in the oxygen radical absorbance capacity (ORAC) and Trolox equivalence antioxidant capacity (TEAC) assays when added at 0.2%. The application of gelatine film containing CD and CS was found to be effective in delaying lipid oxidation and deterioration of beef patty quality during storage. Therefore, the films prepared in this study offered an alternative edible coating for the preservation of fresh food.